Dispersion-managed soliton molecules in a near zero-dispersion fiber laser - Luo, Yiyang (2020)
Physics phenomena of multipulse compounds have enriched the life of ultrashort pulses beyond traditional pulse singlets in passively mode-locked fiber lasers. By developing a near zero-dispersion fiber laser, we report on the generation of dispersion-managed soliton (DMS) molecules. During propagation in the laser cavity, the broadband DMSs experience a breathing process (i.e., periodic compression and stretch of the pulse width), which facilitates various molecule evolutions from pulse singlets. In particular, tightly bound DMS pairs, loosely bound DMS pairs and three-pulse to eleven-pulse molecules are respectively observed. Apart from the aforementioned DMS molecules with equal pulse separations, unequally spaced DMS molecules with different multipulse structures are also obtained, typically including the (2 + 1)-type molecule and the (2 + 3 + 1)-type molecule. The investigation of DMS molecules characterized by versatile multipulse structures is of both fundamental scientific interests in soliton dynamics and potential applications of ultrahigh-capacity optics communications based on advanced modulation formats.